Depressive symptoms can change the lifestyle of the elderly: a cross-sectional case-control study - Cunha, Adriel de Lima (2019)
It was our objective to evaluate the frequency of depressive symptoms, the relationship between sociodemographic variables and lifestyle in the population attending the Third Age Cohabitation Centers. The sample consisted of 75 elderly women (> 60 years old), enrolled and active members (minimum three days a week) of the Third Age Living Center in the Maria Ortiz neighborhood of the city of Vitória / ES. After applying the questionnaire to identify the depressive symptomatology, the elderly were divided into two groups: with (n: 28) and without (n: 47) depressive symptoms. The socio-demographic profile, anthropometric and lifestyle parameters were analyzed. After the analysis of the geriatric depression scale, 28 (37%) elderly had depressive symptoms (8 ± 3 points) and 47 (63%) had no symptoms (2 ± 2 points). No statistical differences (p>0.05) were found between the groups among the anthropometric parameters. Significant differences (p <0.05) were found in the classification of lifestyle, with a higher prevalence of regular style (50%) in the symptomatic group in relation to the asymptomatic group, with 53% being very good. A negative correlation (p<0.0001; r2:0.5779) was found between the scores of depressive symptomatology and lifestyle, indicating a lower presentation of symptoms with proportional improvement in lifestyle. The results found in this study suggest that elderly women with an unfavorable lifestyle present greater depressive symptomatology.